A multi-source based Monte Carlo simulation model for spot scanning proton radiotherapy using GEANT4. (July 2023) - Galanakou, Panagiota; String, Shawn; Shang, Charles; Tahir, Sajjad; Aydogan, Bulent; Muhammad, Wazir
Abstract: Proton therapy is widely used for treating various tumor types due to its favorable dosimetric characteristics compared with conventional radiotherapy. However, a small error in dose calculation may lead to a substantial misadministration of planned radiation dose. This work aims to create a simplified and easy-to-use Monte Carlo (MC) simulation model, based on the multi-source model principle, for spot scanning proton radiotherapy. Our multi-source model contains a set of physical parameters acquired from a Varian ProBeam compact system at the South Florida Proton Therapy Institute (SFPTI). The source model input parameters are mean energy (σΕ ) and beam spot (σs ) standard deviations, which directly affect the integrated depth-dose (IDD) dosimetric characteristics such as beam width, proton range, and distal fall-off. Despite the simplicity of the presented model, all simulated results matched the corresponding experimental values within 2.5% and were found to be within the acceptable clinical limits, for a wide nominal proton energy range (i.e., 90–220 MeV). Additionally, the comparison of the simulated IDDs with the experimental IDDs was found to be highly conformal with 100% of the points passing the 2%/2 mm gamma index test. The model presented in this work can be efficiently used to model high energy (>80 MeV) in a central axis clinical scanning proton beam in a real clinical setting. The small number of input parameters selected allows for a more efficient and user-friendly MC modeling than previously developed models, while off-axis beam characteristics can be studied with the addition of a new sub-source parameter file. Highlights: A simple Geant4 model matches experimental dose depth curves for clinical proton ranges. Tuning inputs; mean proton energy, its standard deviation (std), and the beam spot std. 100% of depth dose points matched the clinical data based on the gamma index test. All simulated results meet the AAPM TG 224 limits except for 70 MeV proton energy.